Hydrogeological and Engineering Investigations of Gully Sites in Zing and Environs, Northeastern Nigeria - Ankidawa, B. A.; Ishaku, J. M.; Ahmadu, S. P. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
The research area is characterized by problems of gully erosion which have resulted in the destruction of roads and uprooting trees of economic importance. Reduction in the area of arable and other agricultural land, which become divided into smaller parcels and leads to increased farming cost. Hydrogeological and engineering investigations were conducted in Zing and environs, Taraba State of Nigeria to characterize the rock materials that aid gully erosion in the area. The methods involve three (3) stages, reconnaissance survey, detailed field mapping and laboratory analysis. The area is underlain by porphyritic granite and Biotite granite. The geologic structures include fractures, dykes, and veins which trend NNW to SSE, NW-SE and NNE to SSW. The results of geotechnical parameters indicate that the plastic limit ranges between 0 to 24.2%, liquid limit ranges from 20.1% to 43.9%, plasticity index ranges between 11.2 to 19.7%. The coefficient of uniformity ranges between 4.2 and 11.5 while the coefficient of curvature ranged between 0.53 and 1.99. The optimum moisture content was from 8.3 to 9.8%, while maximum dry density is from 1.75 to 1.91mg/m³. The angle of internal friction was between 28° to 40°, while the cohesion is between 0 to 54KN/m². The statistical grain size methods gave hydraulic conductivity values ranging from 2.35 x 10-3m/s to 8.64 x 10-5m/s. The hydraulic head distribution map indicates that the gully sites are located in the discharge areas. The discharge areas are characterized by high hydrostatic pressure which decreases effective stress and in turn reduces the shear strength of materials, enhance, internal erosion in form of piping and cave ins in the discharge areas. From the results of the study, recommendations such as sand mining/excavation along the rivers should be avoided, ridging perpendicular to river bank are reduced, dumping of refuse on the river channels and floodplains should be discouraged and houses should not be constructed along the river banks